Compensation Payments for Land Rights in the Construction of the Krueng Baroe Bridge in South Aceh - Cut Tiya Ascasari; Ilyas Ismail; Siti Rahmah (Graha Primera Saintifika, 2026)
The development of infrastructure for public interest requires land acquisition based on the principles of justice, legal certainty, and utility as stipulated in Article 2 of Law Number 2 of 2012 concerning Land Acquisition for Public Interest Development, which includes the principles of humanity, justice, utility, certainty, openness, agreement, participation, welfare, sustainability, and harmony. However, in practice, the implementation of compensation still poses problems, especially regarding the discrepancy between the compensation value and the real market conditions. This is evident in the construction of the Krueng Baro Bridge in South Aceh, where there are discrepancies in land value and public dissatisfaction with the determined value. The purpose of this research is to analyze the implementation of compensation payments for land rights in the construction of the Krueng Baroe Bridge in South Aceh. The research method used is empirical juridical with a sociological legal approach, data obtained thru interviews with the Commitment-Making Officer, the National Land Agency, the Public Appraisal Service Office, as well as the affected community, and reinforced with literature study. The research results show that formally, the implementation of compensation has followed legal procedures, but the execution has not fully reflected substantive justice, as public consultations were not conducted and non-physical losses were not accommodated in the determination of compensation value. The obstacles that arise are multidimensional, including limited land data, weak institutional integration, and low transparency. The resolution efforts that have been undertaken include deliberations and renegotiations between the implementing parties, KJPP, and the community that rejects the compensation.